THE IMPACTS OF BALINESE WOMEN WORKING IN CRUISE SHIP - I Made Darma Oka; I Wayan Pugra (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
The participation rate of Balinese labor in cruise ships over the last years has dramatically increased. The growth of Balinese labor who works on cruise ships in the past four years reached more than 18 percent. This fact seems unique since working there does not only attract Balinese men as happened in the past but also the women. It is happening because they have been prepared themselves in accordance to the competencies and qualifications needed in cruise ships. The present study aimed to analyze the impacts of Balinese women works on cruise ships overview from economic and socio-cultural perspective. The research subjects were Balinese women who used to or were still working in the cruise ships. This research used qualitative data. The collected data started from one Balinese women having experience in the cruise ships and then spread to the other workers. To answer the research questions, data collection was conducted through observation and deep interviews. The data were analyzed by qualitative analysis. The impact of Balinese women working in cruise ships was overviewed from economic and socio-cultural perspectives. The economic perspective likes: Balinese women working in cruise ships able to improve the family economy, and employment for the community directly or indirectly in the cruise ships. The socio-cultural perspective likes: by working in cruise ships able to motivate the other Balinese women to works on cruise ships, with working in cruise ships can open the horizons and the way of thinking society, increase the personal discipline, and then improve the science and technology in tourism especially at cruises, and growth the awareness to conserve the cultural after seeing the variety of cultures in the word